KESADARAN HUKUM SISWA KELAS XII TERHADAP LARANGAN BULLYING DI SMAN 19 SURABAYA - Wahyuningtyas, Tiara; Wijaya, Rahmanu (Kajian Moral dan Kewarganegaraan, 2023)
This research aims to measure the legal awareness of class XII students regarding the prohibition of bullying behavior at SMAN 19 Surabaya. This research uses a quantitative approach with descriptive methods using the sample size was 80 respondents, namely class XII students from SMAN 19 Surabaya. The data analysis technique used in this research is the percentage technique. The results obtained state that the level of legal awareness of class XII students regarding the prohibition of bullying behavior at SMAN 19 Surabaya is in the sufficient category with a percentage of 54%. Based on the results of the questionnaire, the four indicators of legal awareness show the results with the following details are legal knowledge is 61.67% in the sufficient category, legal understanding is 57.41% in the sufficient category, legal attitude is 47.7% in the poor category, legal behavior is 48.86% are in the poor category. This research it was found that good knowledge and understanding of the law does not necessarily guarantee obedient attitudes and behavior. This is due to internal factors such as within the human conscience which is aware of the values in society as well as external factors such as simply being afraid of sanctions, the existence of regulations or even being conditioned.